CONDIȚIILE REALIZĂRII MANAGEMENTULUI TIMPULUI ÎN ÎNVĂȚAREA AUTOREGLATĂ A STUDENȚILOR - Reaboi-Retrachi, Viorica (CEP USM, 2018)
In contextul reformării sistemului de învăţământ reflectat în finalităţile educaţiei din Republica Moldova, au apărut elemente inovatoare susceptibile să genereze un randament sporit al politicilor educaţionale. Astfel, pentru a se ajunge în final la un proces de învaţare viabil, facil şi performant, a fost necesară adoptarea unor principii de acţiune care implică, în ansamblu, managementul timpului, centrat pe formarea şi dezvoltarea personalităţii umane, a abilităţilor şi competenţelor.

The context of the reform of the education system reflected in the educational achievements of the Republic of Moldova, innovative elements emerged that are likely to generate a higher return on educational policies. Thus, in order to finally achieve a viable, easy and performing learning process, it was necessary to adopt action principles that involve, as a whole, time management centered on the formation and development of human personality, abilities and skills
CONDITIONS FOR THE ADMINISTRATION OF TIME MANAGEMENT IN AUTHORIZED EDUCATION OF STUDENTS
Keywords: timp academic; managementul timpului; motivația intinsecă/extrinsecă; automotivarea; academic time; time management; intinse / extrinsic motivation; self - motivation